Does acceptance-based treatment moderate the effect of stress on dietary lapses?. Issue 12 (10th July 2021) - Coffman, Donna L; Oliva, Isabela Batista; Forman, Evan M
Abstract: Weight loss interventions are successful to the extent that participants adhere to calorie-reduced dietary prescriptions and may be undermined by dietary lapses triggered by external or internal factors, such as stress. The purpose of this study was to examine whether an acceptance-based treatment (ABT) versus a standard behavioral treatment (SBT) moderated the effect of stress on dietary lapses. Ecological momentary assessment data were collected from 189 participants who were randomly assigned to either ABT or SBT. Between-subject and within-subject stress were used to predict lapse occurrence along with intervention condition, and the interaction between intervention condition and stress using a generalized linear mixed-effects model. Gender, time of day, and baseline mean lapses/day were included as control variables. Higher mean baseline lapses/day, female gender, and later time of day were significantly associated with increased odds of lapse. Between-subject stress was positively and significantly related to the odds of lapse. Compared to SBT, ABT showed a significant decrease in the odds of lapse at an individual's average level of within-subject stress, but the interaction of intervention condition with within-subject stress was not statistically significant. Participants with high overall stress levels lapsed more frequently than those with low overall stress levels. There was a significant decrease in the odds of lapse for the ABT group at a participant's own average stress level, suggesting that ABT may be beneficial at participants' usual stress levels but when they deviate from their usual stress level, there are no treatment differences.